Convenience, Trust, Sharia Literacy, and Features in Gopay Usage Decisions - Muhammad Hanafi Ritonga; Muhammad Ikhsan Harahap; Nur Santri (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rise of digital financial services has transformed consumer behavior, particularly among younger demographics. Specific Background: Among Muslim students, the adoption of e-wallets like GoPay is influenced not only by general usability factors but also by alignment with Islamic financial principles. Knowledge Gap: However, limited research explores the integration of sharia financial literacy with other adoption drivers in the context of digital wallets. Aims: This study investigates the influence of convenience, trust, sharia financial literacy, and service features on the decision to use the GoPay e-wallet among students at FEBI UINSU. Results: Using a quantitative method with multiple linear regression analysis and a purposive sample of 85 respondents, the study found that all four variables significantly and positively affect GoPay usage decisions, with regression coefficients of 0.373 (convenience), 0.245 (trust), 0.275 (sharia financial literacy), and 0.316 (service features). The adjusted R² of 0.759 indicates that these factors explain 75.9% of the variation in usage decisions. Novelty: This research uniquely integrates Islamic financial literacy into the model of technology adoption in a Muslim student population. Implications: The findings suggest that increasing awareness of sharia-compliant financial practices and enhancing service features may boost digital financial inclusion among Muslim users. Highlights: Integrates Islamic financial literacy into e-wallet adoption analysis. Identifies key drivers: convenience, trust, features, and sharia literacy. Explains 75.9% of usage decision variation among FEBI UINSU students. Keywords: GoPay, Sharia Financial Literacy, E-Wallet Adoption, Muslim Students, Digital Finance